A model of stress concentration factors for external corrosion patches on large-diameter underground cast iron pipes. Issue 1 (2nd January 2023) - Fu, Guoyang; Zhang, Chunshun; Deo, Ravin; Rathnayaka, Suranji; Shannon, Benjamin; Kodikara, Jayantha
ABSTRACT: Field evidence revealed that buried cast iron water pipes can deteriorate through large localized corrosion patches with lengths greater than 1 m, formed by a cluster of small pits. This study investigated the effect of large corrosion patches on the performance of large-diameter cast iron pipes. Although large corrosion patches are highly irregular in nature, they were idealized as semi-ellipsoids. To validate the approximation of corrosion patch geometries with semi-ellipsoids, comparison of finite element models of scanned corroded pipe geometries with the approximated semi-ellipsoidal patches on the same pipes were conducted. Following this validation, parametric studies were performed, which covered a wide range of the pipe and patch dimensions. Based on the finite element analysis, an equation for stress concentration factors was derived and is presented in this paper. This development will significantly assist the pipe engineers and asset managers in the condition assessment of corroded cast iron pipelines.